Fifty Shades of Tolerance: Human Rights Argumentations concerning Family Models and Hate Speech - Csink, Lóránt (Iuris Dictio, 2018)
The protection of human rights is one of the main obligations a state has in order to fulfill its duties. Therefore, the right of freedom of expression shall be protected, especially because it relates directly to the defense of the democratic of a society. Although there are different points of view regarding an issue, especially same-sex marriage, the state is obligated to stay neutral towards public opinions. Consequently, public opinions might end up transforming into hate speech which creates an even larger confrontation within people and the state. This is why, the state must establish fair limits for human rights. Finally, it is essential to understand that promoting tolerance is the most important aspect to safeguard the rights of people to freely speak their minds in order to exercise their right of freedom of speech.
Keywords: Freedom of Expression; Same-sex Marriage; Hate Speech; Protect Minorities